The Impact of Globalization on Content and Subjects in the Curriculum in Madrasah Ibtidaiyah: Challenges and Opportunities - Maria Fatima B. Beribe (P3M IAI Nusantara Batang Hari, 2023)
This research elucidate the impact of globalization on the content and subjects of Madrasah Ibtidaiyah curriculum, focusing on the challenges and opportunities it presents. The study utilizes a combination of literature review and thematic analysis to explore the influence of globalization on the curriculum and the strategies employed by Madrasah Ibtidaiyah to strike a balance between traditional Islamic teachings and global knowledge and skills. The findings reveal that globalization has influenced the content and subjects taught in Madrasah Ibtidaiyah curriculum by necessitating the incorporation of global perspectives, emphasizing universal values, and contextualizing global knowledge within an Islamic framework. However, Madrasah Ibtidaiyah faces challenges in adapting their curriculum, including the need to ensure the preservation of Islamic teachings, addressing cultural sensitivities, and navigating societal expectations. Despite challenges, globalization offers opportunities for Madrasah Ibtidaiyah to enhance their curriculum and prepare students for a globalized world. This includes fostering intercultural communication, promoting global citizenship, encouraging critical thinking, nurturing tolerance and inclusion, and developing cultural sensitivity. The incorporation of global perspectives significantly impacts students' understanding of diversity and multiculturalism by exposing them to different cultures, challenging stereotypes, promoting intercultural communication, and fostering a sense of global citizenship. To achieve a balance between preserving traditional Islamic teachings and integrating global knowledge and skills, Madrasah Ibtidaiyah can employ strategies like integrating universal values, contextualizing global knowledge within an Islamic framework, collaborating with Islamic scholars, emphasizing Islamic history, developing specialized subjects, investing in teacher professional development, and engaging parents and the community.